1000‐kV UHV substation live working and safety recommendations. Issue 9 (10th June 2018) - Fang, Yaqi; Rehman, Habibur; Xiao, Bin; Wu, Tian; Liu, Kai; Wang, Linong
Abstract : This work focuses on the measurement and analysis of the electric field for live working in a 1000‐kV substation. Also, it compares the electric field and the shielding efficiency requirement of a 1000‐kV substation with 1000‐kV transmission lines. The electric field at the ground potential of the substation was measured using a microelectromechanical system (MEMS)‐based device. However, for safety reasons and to acquire rigorous data, finite element method (FEM) was applied to calculate the electric field at equipotential. Two cases of entry into equipotential were considered: one in which the worker moves along tension insulators to live conductors, and another where the worker is lifted to an energized bus bar on an insulated elevating platform. Our results indicate that the electric field values on the worker in the 1000‐kV substation and transmission lines are about the same at ground potential, while at equipotential, the substation's maximum electric field is 25.2% higher outside the conductive clothing and 47.4% higher outside the metallic mask as compared to the 1000‐kV transmission lines. Based on these results, for live working in a 1000‐kV substation, we recommend the use of conductive clothing with 60‐dB shielding efficiency, which is similar to that used in live working on a 1000‐kV transmission line, but the metallic mask should have 25‐dB shielding efficiency, which is 5 dB higher than that used for the transmission line. © 2018 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.